Development and validation of a UPLC‐MS/MS method for the determination of 7‐hydroxymitragynine, a μ‐opioid agonist, in rat plasma and its application to a pharmacokinetic study. (25th July 2013) - Vuppala, Pradeep K.; Jamalapuram, Seshulatha; Furr, Edward B.; McCurdy, Christopher R.; Avery, Bonnie A.
ABSTRACT: A simple, sensitive and specific ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC‐MS/MS) method was developed and validated to determine the concentrations of 7‐hydroxymitragynine in rat plasma. Following a single‐step liquid–liquid extraction of plasma samples using chloroform, 7‐hydroxymitragynine and the internal standard (tryptoline) were separated on an Acquity UPLC TM BEH C18 (1.7 µm, 2.1 × 50 mm) column using an isocratic elution at a flow rate of 0.2 mL/min. The mobile phase consisted of 0.1% acetic acid in water and 0.1% acetic acid in acetonitrile (10:90, v/v). The run time was 2.5 min. The analysis was carried out under the multiple reaction‐monitoring mode using positive electrospray ionization. Protonated ions [M + H] + and their respective product ions were monitored at the following transitions: 415 → 190 for 7‐hydroxymitragynine and 173 → 144 for the internal standard. The calibration curve was linear over the range of 10–4000 ng/mL ( r 2 = 0.999) with a lower limit of quantification of 10 ng/mL. The extraction recoveries ranged from 62.0 to 67.3% at concentrations of 20, 600 and 3200 ng/mL). Intra‐ and inter‐day assay precisions (relative standard deviation) were <15% and the accuracy was within 96.5–104.0%. This validated method was successfully applied to quantify 7‐hydroxymitragynine in rat plasma following intravenous administration. Copyright © 2013 John Wiley & Sons, Ltd.